Social economic and education of national athletes - Ujen Zenal Mikdar; Zuly Daima Ulfa; Roso Sugiyanto (LPMPP Universitas Negeri Yogyakarta, 2023)
The success of becoming a national athlete cannot be separated from various aspects which influence it, they are internal aspects, coaching and training, social environment, family, education, sociocultural, and other factors. The purpose of this research is to identify the national athlete profiles from their socioeconomic and educational aspects. This research was categorized into descriptive qualitative research involving eight participants from national athletes in Palangka Raya, Central Kalimantan. The results of the study showed that the social attitude of the athlete's achievements was due to their disciplines, high willpower, determination to win, self-confidence, fighting, hard work, perseverance, patience, and prayer. In addition, based on the economic aspects, the athletes have the opportunity to become civil servants; get some money, land lots, and a house; be more convenient to choose a school; and have the opportunity to go Hajj and travel abroad. The research also showed that most of them are high school graduates, some are still in college and some of them are college graduates. As national athletes, they must be able to manage the time between training and studying, especially when they are taking part in training camps and matches.